Labour regulations in India: Improving the social security framework - Anwarul Hoda; Durgesh K. Rai (Indian Council for Research on International Economic Relations (ICRIER), 2017)
An important segment of labour regulations concerns the protection aspects of social security. These regulations provide safety nets or fall back mechanisms to enable workers to cope with crises that affect households from time to time, such as illness, employment injury, death or old age. This paper critically reviews and analyses existing regulations in India that provide fall back mechanisms and evaluates how they compare with systems in selected comparator countries and measure up against the minimum standards recommended in various ILO Conventions. These regulations are important not only from the point of view of the welfare of society but also from the perspective of efficiency of the work force in any activity. The analysis reveals serious shortcomings in the social security legislation and programmes in the country insofar as they apply to the unorganised workers. The paper concludes by making recommendations on alternative approaches to redress the deficiencies.
Keywords: J32; J88; 330; Labor regulations; social security; ILO Conventions; India